2021
DOI: 10.1371/journal.pgen.1009868
|View full text |Cite
|
Sign up to set email alerts
|

The H3.3K27M oncohistone affects replication stress outcome and provokes genomic instability in pediatric glioma

Abstract: While comprehensive molecular profiling of histone H3.3 mutant pediatric high-grade glioma has revealed extensive dysregulation of the chromatin landscape, the exact mechanisms driving tumor formation remain poorly understood. Since H3.3 mutant gliomas also exhibit high levels of copy number alterations, we set out to address if the H3.3K27M oncohistone leads to destabilization of the genome. Hereto, we established a cell culture model allowing inducible H3.3K27M expression and observed an increase in mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 95 publications
2
20
0
Order By: Relevance
“…By dissecting how H3.3 mutants skew DNA repair, we show that mutations in core chromatin components induce genome instability by dysregulating the recruitment of repair factors at damaged RF (Figure S4D). Aberrant repair of damaged RF leads to mitotic aberrations (Berti et al, 2020), which were recently reported in cells expressing the H3.3K27M mutant (Bočkaj et al, 2021) and is the likely cause of genome instability. The influence of co-occurring genetic alterations (Mackay et al, 2017) on this phenotype should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…By dissecting how H3.3 mutants skew DNA repair, we show that mutations in core chromatin components induce genome instability by dysregulating the recruitment of repair factors at damaged RF (Figure S4D). Aberrant repair of damaged RF leads to mitotic aberrations (Berti et al, 2020), which were recently reported in cells expressing the H3.3K27M mutant (Bočkaj et al, 2021) and is the likely cause of genome instability. The influence of co-occurring genetic alterations (Mackay et al, 2017) on this phenotype should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Besides their effect on gene expression, pHGG H3.3 mutations also promote genome instability (Bočkaj et al, 2021; Fang et al, 2018; Haase et al, 2022; Pfister et al, 2014; Schwartzentruber et al, 2012; Sturm et al, 2012; Yadav et al, 2017), which is one of the major drivers of cellular transformation (Hanahan, 2022). In particular, H3.3 mutant pHGGs display increased copy number alterations and chromosomal rearrangements compared to wild-type (WT) H3.3 tumors (Bočkaj et al, 2021; Mackay et al, 2017; Schwartzentruber et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed consent was given, and local ethics committee approval was granted for use of the patient material. The scWGS and analysis were performed as described previously [ 33 , 56 , 57 ]. Anonymized reads of the medulloblastoma samples are deposited at the European Nucleotide Archive/ENA ( , accessed on 24 July 2022), accession number PRJEB54865.…”
Section: Methodsmentioning
confidence: 99%
“…In solid tumors, mutant chromatin remodelers differentially recruit histone modifiers that confer chemoresistance (Drosos et al, 2022). These cancer-associated mutant histones are referred to as oncohistones, which are now emerging as a class of prominent biomarkers of cancers (Bočkaj et al, 2021). In this review, we address the molecular and mechanistic underpinnings of nuclear envelope factors, their crosstalk with chromatin, and their pivotal role in cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%